2004
DOI: 10.1158/0008-5472.can-03-4040
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Novel Sonic Hedgehog Gene Mutations Identified in Basal Cell Carcinomas from Xeroderma Pigmentosum Patients

Abstract: Altered sonic hedgehog (SHH) signaling is crucial in the development of basal cell carcinomas (BCC), the most common human cancer. Mutations in SHH signal transducers, PATCHED and SMOOTHENED, have already been identified, but SHH mutations are extremely rare; only 1 was detected in 74 sporadic BCCs. We present data showing unique SHH mutations in BCCs from repair-deficient, skin cancer-prone xeroderma pigmentosum (XP) patients, which are characterized by high levels of UV-specific mutations in key genes involv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
20
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(20 citation statements)
references
References 47 publications
0
20
0
Order By: Relevance
“…The sonic hedgehog (Shh) signaling pathway has been demonstrated to regulate embryo development and tumor cell proliferation in several human neoplasms, such as the prostate, pancreas and skin carcinomas [7,8,9,10]. Shh is a member of the hedgehog family that was originally identified by its homology to the Drosophila melanogaster segment polarity gene, hedgehog.…”
Section: Introductionmentioning
confidence: 99%
“…The sonic hedgehog (Shh) signaling pathway has been demonstrated to regulate embryo development and tumor cell proliferation in several human neoplasms, such as the prostate, pancreas and skin carcinomas [7,8,9,10]. Shh is a member of the hedgehog family that was originally identified by its homology to the Drosophila melanogaster segment polarity gene, hedgehog.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies suggest that the hedgehog (Hh) signal pathway contributes to cell proliferation and differentiation in several human neoplasms, such as pancreas, prostate and skin carcinomas. (6)(7)(8) The Hh gene was first identified in the embryonic development of Drosophila. (9) The Hh signal transduction pathway controls a variety of developmental processes such as proliferation, differentiation and organogenesis.…”
mentioning
confidence: 99%
“…(9)(10)(11) It is known that Gorlin's syndrome, which is associated with abnormal activation of the Hh signal pathway mainly due to Ptch mutation, shows an increased incidence of basal cell carcinoma, medulloblastma and rhabdomyosarcoma. (8,12) There are no available data on the expression of Hh signal molecules in human epithelial ovarian neoplasms. Therefore, in the present study we first investigated immunohistochemically the expression of Hh molecules, such as Shh, Ihh, Dhh, Ptch, Smo and Gli1 proteins, in benign, borderline and malignant ovarian tumors and normal ovarian surface epithelium (OSE), and correlated the expression of each with cell proliferative activity assessed by Ki-67 staining, clinicopathological parameters and patient outcomes.…”
mentioning
confidence: 99%
“…Therefore it is not surprising that activating SMO mutations have been detected in a number of sporadic BCCs [31]. Recently, CouvePrivat et al [4] identified SHH missense mutations in BCCs from xeroderma pigmentosum patients. All the BCCs with SHH mutations also had alterations in either SMO or PTCH, indicating that the SHH mutations may represent an additive effect on the oncogenic potential.…”
mentioning
confidence: 99%